Updates on the Management of Ocular Vasculopathies with VEGF Inhibitor Conbercept. (1st December 2020) - Liu, Huan; Ma, Yue; Xu, Hong-Chang; Huang, Li-Ying; Zhai, Li-Ying; Zhang, Xiao-Rong
ABSTRACT: Purpose : To provide a detailed review on the therapeutic efficacy of conbercept for the management of ocular vasculopathies. Methods : A comprehensive literature search of various electronic databases was performed. Results : Ocular vasculopathy is one of the major causes of visual impairment and blindness which includes a range of disorders. Vascular endothelial growth factor (VEGF) regulates angiogenesis, enhances vascular permeability, and drives the formation of neovascularization. Anti-VEGF therapy has been shown to prevent vision loss or potentially improve vision in patients with exudative or neovascular retinal disease. The most recent anti-VEGF drug in China is conbercept. In the USA and Europe, bevacizumab is the most recently approved anti-VEGF agent. Conclusions : Conbercept serves as another anti-VEGF option for patients with neovascular AMD and other retinal vascular disorders. There have not been many clinical trials that study conbercept as compared with other currently available anti-VEGF drugs. There is a need for large-scale, well-designed, randomized clinical trials to ensure its long-term safety and efficacy and to determine if it has any advantages over other anti-VEGF agents.